The Career Paths of Illegitimate Scottish Clergy: The Evidence of the Registers of the Apostolic Penitentiary, the Registers of Supplications and Lateran Registers - McDonald, Jennifer R. (Florilegium, 2008)
The lack of native ecclesiastical sources has seriously impeded research on the medieval Scottish Church and its clergy, although evidence from the papal archives — in particular, material from the Registers of Supplications, Lateran Registers, and the archives of the Papal Penitentiary — has helped to overcome this problem to some extent. While the Registers of Supplications and Lateran Registers provide information about ordained clergy and the benefices that they obtained, the Penitentiary archives are particularly useful for analysis of clerical recruitment, training, and ordination. The present article demonstrates how analysis of these sources, and of others such as matriculation records, can be used to trace the career paths of supplicants. Using Scottish Penitentiary supplicants who applied for dispensation from illegitimacy, the article demonstrates differences in career paths and mobility within the Scottish ecclesiastical hierarchy.